Mean girls [videorecording (DVD)] - Waters, Mark S., 1964-; Lohan, Lindsay, 1986-; McAdams, Rachel, 1978-; Fey, Tina, 1970-; Fey, Tina, 1970-; Wiseman, Rosalind, 1969- (Paramount, 2017)
Having been home-schooled and raised in the African bush, Cady is unprepared for the cut-throat politics of public school.